PERAN BKPM DIY DALAM MENGELOLA PENANAMAN MODAL ASING SEBAGAI PENDORONG PEREKONOMIAN DIY (2008-2013) - Hendy Indra Utama (HI 15 UMY 261, 2015)
*261 Foreign investment is one of international cooperation form which conducted by international relations actor, includes DIY Government (BKPM). The realization of foreign investment in DIY can help their economy growth in Global Financial Crisis 2008. But if not managed properly, foreign investment can cause of various problems. And DIY Government (BKPM) did important role to manage it. First as an initiator in establishing international cooperation, second with formulating and implementing the General Plan Investment Policy, and third created the conducive conditions of investment environment. Finally, DIY economic problems can be resolved.